THE OPERATION IN TIME OF THE STATUTE OF FRAUDS AND OF THE STATUTE OF LIMITATIONS - Côté, Louis (Revue de droit de l'Université de Sherbrooke, 1985)
This article is concerned with the operation in time of two specific Statutes: The Statute of Frauds and The Statute of Limitations.In a first step, the principles applicable to the operation in time of those two Statutes are traced back to their common law origins. At that stage of the paper, it is realized that the principles originally enunciated attached to the Statute in respect of which they had been propounded, without any interconnection.Then, it is seen that a certain streak of cases has, for all practical purposes, merged the said principles, thereby operating a break in the quasi-absolute separation characterizing the more or less exclusive links that previously existed between the Statute concerned and the principles regulating its operation in time.In a further step, however, it is concluded, from certain cases, that the merger of the principles under study should probably have never taken place, the Statutes to which they were originally respectively applied being very different the one from the other.Still further, at the conclusion of that common law analysis, hypotheses are made as to what might have been the effect of the Federal Interpretation Act had the provisions of that Act been applied to some of the cases covered in this article.Finally, conclusions are drawn from the entire paper and a suggestion is made that the Federal Interpretation Act be amended.